Direct Estimation of Lead in Solder Alloy Using A Novel Coated Wire Pb(II) ISE - Jaya Kumari, P.; Chattopadhyaya, M.C. (Asian Journal of Chemistry, 2010)
A new heterogeneous Pb(II) ion-selective coated wire electrode (CWISE) based on lead (II)-violuric acid complex as electroactive material has been described. The working pH range of the electrode is 2-5. The electrode shows a linear response in the concentration range 1 x 10-1 to 5 X 10-6 mol dm-3• The response time of the electrode is 10 seconds. The electrode is selective for Pb(II) ions in the presence of number of cations such as Cu(II), Ni(II), Fe(III), Zn(II) and Ca(II). The electrode was used for direct determination of lead in the sample of solder.